A study of the efficacy and safety of the balloon tamponade in the management of atonic post-partum hemorrhage - Kumar, Aruna; Kachchhap, Khushboo; Shrivastava, Shubha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The most common cause of post-partum hemorrhage (PPH) is uterine atony. Treatment for atony follows a well-defined stepwise approach, including drugs and mechanical interventions followed by surgery as a last resort. Early use of intrauterine balloon tamponade is a way of limiting ongoing uterine blood loss while initiating other measures and can be readily implemented by providers with minimal training. Methods: This prospective interventional study was conducted in 112 consecutive patients attended department of obstetrics and gynecology, Gandhi Medical College and Associated Sultania Zanana Hospital, Bhopal, Madhya Pradesh, India, in one year of study period. Results: In this study most of the patients had gestational age >37 weeks [83 (74.1%)]. Most of the patients in the study had vaginal delivery [64 (57.1%)]. In 84 (75%) patients Bakri balloon was used followed by Burke balloon in 17 (15.2%) patients, condom catheter in 7 (6.2%) patients and CG balloon in 4 (3.6%) patients. Different types of balloons were used according to availability of balloon at the time of management. Most of the patients [71 (63.3%)] had trans-vaginal route of balloon placement and 41 (36.7%) patients underwent trans-abdominal balloon placement. Most of the patients 69 (61.65%), responded to tamponing within 20 minutes of balloon placement while 9 patients had negative tamponade and continued to bleed. Bakri balloon tamponade was most commonly used in 84 (75.0%) patients. CG balloon and condom catheter were used only in 4 (3.6%) and 7 (6.3%) patients respectively. Tamponading was effective and successful in 103 (92%) patients. Conclusions: PPH is still a leading but preventable cause of maternal morbidity and mortality. In the majority of cases, relatively simple methods are used to avert a disaster, although these are not always employed. Uterine tamponade using intrauterine balloons appears to be an effective tool in the management of PPH.